(untitled) (Journal of Global Accounting, 2023)
The main aim of this study is to find out the effect of board gender diversity on financial performance of listed deposit money banks in Nigerian Stock Exchange (NSE) as at December, 2017. Specifically, it investigated the extent to which board gender diversity affects return on asset and return on capital employed of selected quoted deposit money banks in Nigeria. In pursuit of the objectives of this study, two hypotheses were formulated and tested using secondary data obtained from the firms’ annual report and fact book. Data were analyzed using simple regression analytical estimation technique with aid of E-view 9.0 which was used in determining the effect of board gender diversity on financial performance of selected quoted deposit money banks. The findings of this study confirmed that two hypothesis tested are significant. Therefore, the researcher recommends that sound policy should be in place to ensure that the proportion of female as well as financially knowledgeable in company’s board is high to increase the reporting quality of financial performance.